Graph-based algorithmic design and decision-making framework for district heating and cooling plant positioning and network planning. (October 2021) - Ho, Chi-On; Nie, Ting; Su, Lingqi; Yang, Zheng; Schwegler, Ben; Calvez, Philippe
Highlights: Algorithmic design and decision-making framework for district energy system. District heating and cooling site location and network layout optimization. Multi-objective evaluation and data-driven decision support. Graph-based approach for district heating and cooling system design. Abstract: Although buildings are the single largest users of energy in cities, many individual building HVAC (heating, ventilation, and air conditioning) systems are energy inefficient. Sustainable district heating and cooling systems have been developed to address this inefficiency, however, the implementation of district heating and cooling systems is a complex, capital intensive multivariate problem. One critical engineering problem, the location of energy production plant and pipe network topology, has a major influence on the system performance as well as the life cycle cost, and therefore should be comprehensively studied and chosen. This paper proposes a novel algorithmic design and decision-making framework that uses multiple simultaneous criteria to generate and evaluate design alternatives of site selection and pipe network layout. The framework consists of three components: site location and topology generation, network sizing and evaluation, and multi-objective decision-making assistance. The proposed framework has been validated in a real-world district cooling greenfield project in China's metropolitan area. Results were compared against the engineers' best practices. It has shown that the proposed framework could find equally good or better designs in engineering and financial performance with CAPEX reduction of up to 15%.